Effect of using the conversation project as a teaching tool to increase graduate student nurses' self confidence in discussing end-of-life wishes with patients and families - O'Sullivan, Cynthia; O'Shea, Eileen (Nursing Research, 2019)
Keywords: dept.nur; peer-reviewed; ⛔ No DOI found

Evaluation of an innovative curriculum enhancement: The conversation project - Pagano, Michael; Manger, Diana R.; O'Shea, Eileen; O'Sullivan, Cynthia (Nursing Education Perspectives, 2020)
Two northeast nursing schools piloted an innovative curriculum to teach The Conversation Project (TCP) to the next generation of nurses. The goal was to educate 26 graduate nursing students about how to have end-of-life and advance care planning conversations with people before they experience a crisis. The focus of assignments was on communicating newly learned TCP information. Postreflections demonstrated that participants felt their communication skills had been enhanced while their anxieties were reduced. The students' abilities to have end-of-life conversations increased. © Lippincott Williams & Wilkins.
Keywords: Advance Care Planning; Communication; Conversation Project; Curriculum; End-of-Life Care; Graduate Nursing Education; Humans; Learning; Schools, Nursing; Students, Nursing; adult; advance care planning; anxiety; article; clinical article; communication skill; conversation; curriculum; dept.nur; female; graduate nursing student; human; interpersonal communication; learning; male; nursing education; nursing student; peer-reviewed

Psychological distress during ovarian cancer treatment: improving quality by examining patient problems and advanced practice nursing interventions - O'Sullivan, Cynthia Kline; Bowles, Kathryn H.; Jeon, Sangchoon; Ercolano, Elizabeth; McCorkle, Ruth (Nursing Research and Practice, 2011)
Keywords: dept.nur

Nursing students' access to test banks: are your tests secure? - Madara, Bernadette; Resha, Cheryl; Krol, Maria D.; Lacey, Kimberly; Martin, Elaine F.; O'Sullivan, Cynthia; Smith, Jan Weingrad (Journal of Nursing Education, 2017)
Background: Schools of nursing have moved to multiple choice test questions to help prepare students for licensure and practice. However, students can buy test banks to help them “get through” nursing school. Accurate assessment of nursing students' knowledge and judgment comprises access to test banks. Method: The purpose of this exploratory study was to gain an understanding about nursing faculty's knowledge concerning test bank security issues, to assess whether publishers were aware of this issue, and vendor's reasons for supplying test banks to students. Results: Overall, the results indicated that the majority of faculty were unaware of student access to test banks, and although most do not use test banks verbatim, general consensus existed that test bank security is a concern. Conclusion: Implications include increasing faculty awareness of test bank access by students, supporting educators to develop their own test bank items, and promoting security of all examinations.
Keywords: Attitude of Health Personnel; Commerce; Databases as Topic; Education, Nursing; Educational Measurement; Faculty, Nursing; Humans; Internet; Surveys and Questionnaires; awareness; commercial phenomena; consensus; data base; dept.nur; education; exploratory research; health personnel attitude; human; human experiment; nursing; nursing education; questionnaire; student; university